Preparing international ICT students for the global workplace: An Australian experience - Briguglio, Carmela; Dell, Peter (International Association for Development of the Information Society, 2010)
Globalisation is leading to an increasing incidence of multinational/multicultural work teams across the globe. This is particularly the case in the world of business, where English also dominates as the most commonly used language in intercultural situations. This paper describes a project which aimed to prepare English as a Second Language (ESL) students for the English speaking work environment in Australia. Information Systems majors in their final year of a Bachelor of Commerce degree at Curtin University of Technology in Western Australia undertook a specially-designed, preparatory two-day intensive communication skills program, followed by a 16-week work placement in large local companies.The preparatory program aimed to give students socio-linguistic knowledge and skills for formal and informal work related contexts. Students were also required to engage in a reflexive activity, which they discussed with a member of the project team, whom they met on a regular basis. Evaluation of the program indicates that structured intervention can assist ESL students to prepare for an English-speaking workplace, particularly in developing confidence. However, a shorter preparatory program, coupled with more targeted support, is likely to be more effective if spaced out over the period of the internship, and addressing particular workplace needs and dilemmas as they arise.